Etched nanoholes in graphitic surfaces for enhanced electrochemistry of basal plane. (October 2017) - An, Hongjie; Moo, James Guo Sheng; Tan, Beng Hau; Liu, Sheng; Pumera, Martin; Ohl, Claus-Dieter
Abstract: The understanding and tailoring of the electrochemistry of graphite is of significant industrial importance. We develop a method of etching pits into the basal planes of highly oriented pyrolytic graphite (HOPG) by electrolysis. The etching of HOPG was realized by performing electrochemical reactions at alternating potentials at room temperature, and the resulting membranes are characterized using atomic force microscopy, scanning electron microscopy, X-ray photoelectron spectra, X-ray diffraction, Raman spectroscopy, Fourier transform infrared spectrscopy, and cyclic voltammetry. Etching only occurs when the electrolysis at negative bias is followed by a brief switch to a positive bias. The size of the etched pits can be tuned by varying the applied potential and reaction time, with deeper pits formed with increased redox cycles and reaction time. Cyclic voltammetry reveals that the electrochemical performance is enhanced greatly as etching progresses due to exposure of edge sites. For its ease of application, efficiency and low cost, our wet etching approach has great promise as a method to develop high active electrodes and nanoporous membranes at large scales for various industrial applications. Graphical abstract: